SISTEM PENDUKUNG KEPUTUSAN DALAM PENILAIAN KINERJA PERAWAT MENGGUNAKAN METODE PROMETHEE PADA PUSKESMAS RENA KANDIS KABUPATEN BENGKULU TENGAH - Alfahmi Muhammad Arif; Kusrini Kusrini; Eko Pramono (Jurnal Informa : Jurnal Penelitian dan Pengabdian Masyarakat, 2019)
The UPTD Puskesmas is a health organization that functions as a center for community health development which also fosters community participation in providing complete and integrated services for communities in the region involved in the form of main activities. UPTD Puskesmas Rena Kandis is a technical implementation unit to support the operations of the Health Office in the field of public health services. In the decision making system the performance evaluation of nurses uses the Promethee method. Where promethee is one method of determining sequence or priority in MCDM (Multi-Criteria Decision Making). The use of the Promethee method is to determine and produce decisions from several alternatives. Taken all data combined into one with the weight of the score that has been obtained through an assessment of the test results. Decision support system is not a decision-making tool, which is a system that helps decision making with data that has been made relevant and needed to make decisions about problems more quickly and accurately. Deciding this system does not agree to make decisions in the decision-making process. The final results obtained from the company using the Promethee method are obtained by comparing with one another then looking for a deviation value in order to be able to calculate the value of the left flow, enter the flow and net flow. The results of the research that has been done, the method of employee promethee is the final result obtained is the result of several alternatives.